Analisis Nilai Karakter Peduli Lingkungan dan Peduli Sosial dalam Cerita Anak â€œPrincess Cinderellaâ€ - Ghina Amalia Dewi; Sucipto Sucipto; Lovika Ardana Riswari (Journal Prakarsa Paedagogia, 2023)
Society's view of the story "Princess Cinderella" only includes cruel stepmother stories and love stories and is not suitable for children to read. However, there are elements that need to be examined and exposed more, namely the values of environmental care and social care in this story. The method used in this research is discourse study, with listening techniques and content analysis in data collection, and the analysis techniques are data reduction, data presentation, and verification. This study presents the results that the story "Princess Cinderella" contains environmental care character values and social care character values; and this story is suitable for children to read to develop the character values of caring for the environment and social care. In conclusion, the story "Prinsess Cinderella" deserves to be read by children with the assistance of their parents, so that the values of caring for the environment and social care can be conveyed properly.Â